Metallothionein 1: A New Spotlight on Inflammatory Diseases - Dai, Hanying; Wang, Lu; Li, Lingyun; Huang, Zhong; Ye, Liang (Frontiers in Immunology, 2021)
MT1 has been demonstrated to be an essential stress protein in maintaining physiological balance and regulating immune homeostasis. While the immunological involvement of MT1 in central nervous system disorders and cancer has been extensively investigated, mounting evidence suggests that MT1 has a broader role in inflammatory diseases and can shape innate and adaptive immunity. In this review, we will first summarize the biological features of MT1 and the regulators that influence MT1 expression, emphasizing metal, inflammation, and immunosuppressive factors. We will then focus on the immunoregulatory function of MT1 on diverse immune cells and the signaling pathways regulated by MT1. Finally, we will discuss recent advances in our knowledge of the biological role of MT1 in several inflammatory diseases to develop novel therapeutic strategies.